The press as a source for the study of the national-state policy of the Bolshevik party in the North Caucasus during the socialist modernization of the region - Lema A. Turpalov; Zarina M. Alkhastova (Кавказология)
The leading instrument of ideological support of the proletariat dictatorship in the Russian national regions after the October revolution in 1917 served the local press, which was formed and functioned under the control of the Bolshevik party. Especially difficult was strengthening Soviet power in the North Caucasus because socialist ideas were unknown and poorly understood by the highlanders. Bolsheviks propagated, first through the local press, the slogan of the right of nations to self-determination to attract the mountain peoples to their side. Large-scale propaganda of the national policy of the Bolshevik Party was carried out in the pages of newspapers and magazines. Meanwhile, publications devoted to these issues in periodicals during the first decades of the Soviet power have been insufficiently studied in the Caucasus studies. At the present stage of historical-journalistic science, the need to rethink the provisions and conclusions of scholarly works of the recent Soviet past has increased. The article attempts to reveal the peculiarities of coverage in the North Caucasus regional press of the Bolshevik party policy in the sphere of national-state building during the Bolshevik totalitarian regime, based on the critical understanding of the published scientific literature, the study of archival materials, content analysis of regional newspapers and magazines.